IMPLEMENTASI 5 PILAR CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PT. PJB UBJOM PACITAN - Asfira Rachmad Rinata; Alfian Dika Pranata; Fathul Qorib (Unitri Press, 2022)
The implementation of CSR is important for companies to balance between aspects of economic, social, and environmental communities. This study aims to determine the implementation of CSR and what are the supporting factors and inhibitions of PT CSR implementation. PJB UBJOM Pacitan. The method used is qualitative with data collection through observation, interview, and documentation. Results of this study explain that PT. PJB UBJOM Pacitan has implemented CSR in various aspects, including employee training and certification, community empowerment in the economic field, distribution of street lighting, implementation of handling management systems, and building conservation turtles and water. The target of the program also includes the village, sub-district, and the district. Community enthusiasm and support from the government are supporting factors in CSR, while the lack of budget and social jealousy are factors inhibiting CSR. In the future, it is necessary to set long-term and short-term targets in CSR implemented and the programs implemented are well focused on empowerment. Penerapan CSR penting dilakukan bagi perusahaan guna menyeimbangkan antara aspek ekonomi, sosial, dan lingkungan masyarakat. Penelitian ini bertujuan untuk mengetahui implementasi CSR serta apa faktor pendukung dan penghambat implementasi CSR PT. PJB UBJOM Pacitan. Metode yang digunakan adalah kualitatif dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian ini menjelaskan bahwa PT. PJB UBJOM Pacitan telah menerapkan CSR di berbagai aspek, meliputi pelatihan dan sertifikasi karyawan, pemberdayaan masyarakat di bidang ekonomi, pemerataan penerangan jalan, penerapan sistem manajemen penanganan, serta membangun konservasi penyu dan air. Sasaran program yang dijalankan juga mencakup pada tingkat Desa, Kecamatan, hingga Kabupaten. Antusias masyarakat dan dukungan dari pemerintah menjadi faktor pendukung dalam CSR, sedangkan minimnya anggaran dan kecemburuan sosial menjadi faktor penghambat CSR. Untuk kedepannya, perlu menentukan target jangka panjang dan jangka pendek dalam CSR yang diterapkan dan program yang diterapkan baiknya berfokus pada pemberdayaan.